Interim results of work package number four (patient safety indicators and vocabulary) of the SIMPATIE project - Bourek, Aleš (ICEQ, 2007)
Overview The objective of SIMPATIE (Safety Improvement for Patients in Europe) collaboration is use of Europe-wide networks of organizations, experts, professionals and other stakeholders to establish, within two years, a common European set of vocabulary, indicators, internal and external instruments for improvement of safety in health care. The SIMPATIE project started the 15th of February 2005. It has a duration of two years and is being executed within the European Commission – Health programmes. Methodology The project is divided into 8 work packages (WP) that aim for more specific objectives together contributing to the overall project objective. This presentation relates to WP4 - Vocabulary & Indicators. Based on literature review, targeted information gathering and expert consultation, taking into account previous work done by the project partners, the WP defined: • A vocabulary (set of definitions) related to patient safety, considering language, health care system organization and economy and cultural issues across Europe • A set of indicators / outcome measures that can be used in efforts to improve patient safety both at the system and organization level. The expert group of WP4 consisted of the following members: Ian Callanan - Irish Society for Quality and Safety in Healthcare, Christian Thomeczek - G-I-N, Georges Maguerez - HAS, Solvejg Kristensen -The County of Aarhus/ ESQH-office for Quality Indicators, Aleš Bourek U-CeKZ, Kaj Essinger - HOPE, Joergen Hansen - The Danish National Board of Health, Jannes van Everdingen - CBO, Rosa Sunol - Avedis Donabedian Foundation, Johan S. de Koning - RIVM, Jacob Anhoej - The Danish Society for Patient Safety, Paul Bartels - The County of Aarhus/ ESQH-office for Quality Indicators, Jan Mainz - ESQH-office for Quality Indicators. All ongoing work is coordinated by Solvejg Kristensen from the ESQH-office for Quality Indicators, Aarhus, Denmark. Sources and literature for vocabulary and indicators assessed include: Australian Commission for Safety and Quality in Health Care (ACSQHC), Agency for Healthcare Research and Quality (AHRQ), Brian Jarmanns Indicators (BJ), The Good Medical Department, Denmark (DGMA), European Community Health Indicator Monitoring (ECHIM), Institute of Healthcare Improvements (IHI), Institute of Medicine (IOM), Joint Commission on accreditation in Health Care (JCAHO), Joint Commission International (JCI), Nordic Indicators (NI), Organisation for Economic Co-operation and Development (OECD), Performance Assessment Tool for Quality improvement in Hospitals (PATH), Veterans Affairs (VA), World Health Organization (WHO). The assessment of patient safety can be carried out through both qualitative and quantitative methods. The quantitative approach uses indicators and epidemiological methods of analysis to systematically quantify distinct aspects safety. PSI serve different purposes, they make it possible to: Survey and monitor the impact of patient safety activities; Document dimensions of patient safety; Make comparison over time (benchmarking); Make judgement and set priorities for developing patient safety; Develop preventive action plans for improving patient safety; Support accountability, regulation and accreditation; Support general internal safety improvement within wards, departments or hospitals. Their use provides a basis for clinicians, management, organisations, providers and health planners aiming to achieve improvement in patient safety. However the use of PSIs is not an exhaustive measure of patient safety, because patient safety is complex and multidimensional. Creating a picture of an organisations patient safety requires using many different measures. Results Concerning the vocabulary: the work package defines a set of 24 definitions related to patient safety, considering language, health care system organization and economical and cultural issues across Europe. Concerning the PSI: PSI indicators have been expertly reviewed and classified into following categories - Immediately applicable across EU; Applicable with a defined restriction and/or within certain EU healthcare systems; Recommended for future decision on implementation in EU after revision; Not suitable for various reasons in EU environment. Interim project materials will be presented at this conference with emphasis on demonstrating the methodology used. More in-depth materials may be found at http://www.simpatie.org .